2016
DOI: 10.1002/jsfa.7759
|View full text |Cite
|
Sign up to set email alerts
|

Glycolipid biosurfactants: main properties and potential applications in agriculture and food industry

Abstract: Glycolipids, consisting of a carbohydrate moiety linked to fatty acids, are microbial surface active compounds produced by various microorganisms. They are characterized by high structural diversity and have the ability to decrease the surface and interfacial tension at the surface and interface, respectively. Rhamnolipids, trehalolipids, mannosylerythritol lipids and cellobiose lipids are among the most popular glycolipids. They have received much practical attention as biopesticides for controlling plant dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
79
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(90 citation statements)
references
References 111 publications
0
79
0
5
Order By: Relevance
“…The high molecular weight biosurfactants include the lipopolysaccharides but those of main interest are the low molecular weight glycolipids and lipopeptides (LPs) and phospholipids. Of the glycolipids (Mnif and Ghribi ), which include trehalolipids, cellobiose lipids, mannosylerythritol lipids (MELs), rhamnolipids, (derived from mainly Pseudomonas ) and sophorolipids (SLs), (derived from Candida and related species) are of the most interest. The glycolipids (Marchant and Banat ) and the LPs (derived mainly from Bacillus sp.)…”
Section: Classification and Structure Of Microbial Biosurfactants Of mentioning
confidence: 99%
See 2 more Smart Citations
“…The high molecular weight biosurfactants include the lipopolysaccharides but those of main interest are the low molecular weight glycolipids and lipopeptides (LPs) and phospholipids. Of the glycolipids (Mnif and Ghribi ), which include trehalolipids, cellobiose lipids, mannosylerythritol lipids (MELs), rhamnolipids, (derived from mainly Pseudomonas ) and sophorolipids (SLs), (derived from Candida and related species) are of the most interest. The glycolipids (Marchant and Banat ) and the LPs (derived mainly from Bacillus sp.)…”
Section: Classification and Structure Of Microbial Biosurfactants Of mentioning
confidence: 99%
“…Previous reports on the effectiveness of B. subtilis SPB1 strain (HQ392822) revealed a wide spectrum of actions including antimicrobial activity towards micro‐organisms with MDR profiles (Ghribi et al . ), antifungal activity against phytopathogenic fungi (Mnif and Ghribi ) and antidiabetic and antilipidemic properties in alloxan‐induced diabetic rats (Zouari et al . ).…”
Section: Health‐related Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was shown that sophorolipids (SLs), which are types of biosurfactants, have potential applications in agriculture and the food industry and are effective for control of pathogenic bacteria (Mnif & Ghribi, 2016). Sophorolipids (SLs) are a type of biosurfactants and are extracellular glycolipids that are composed of sophorose (a disaccharide, 2-O-b-D-glucopyranosyl-b-D-glucopyranose) connected via a b-glycosidic linkage between the 1 0 hydroxy group of the sophorose and an x or x-1 hydroxy group located on the fatty acid.…”
Section: Introductionmentioning
confidence: 99%
“…Oligosaccharides and glycoconjugates, in the form of free sugars and glycolipids, are crucial in influencing the properties and functions of materials that include lecithin . High levels of oligosaccharides could induce a browning reaction and infusion reactions in such materials when stored and used for medical purposes.…”
Section: Introductionmentioning
confidence: 99%